(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Paper aims to analyse operational risk of Brick work, Plaster works, Plumbing works and Painting works of different high rise building construction projects within Kathmandu , Nepal. The data were collected from the workers and the site management team through questionnaire survey and direct observation. Data were analysed, interpreted and presented using simple descriptive statistics, tables, bar charts and pie charts. Risk level of Painting works was the highest with risk score of 18.0 among all four types of job under study. Brick works and plaster works was the highest with 16 and 13.125 risk score respectively. So, both considered as “High risk”. Plumbing works had been found to have the highest risk score of 9.75 and having risk rating level of “Moderate”. Risk level of activity, working on scaffolding had been revealed as the highest for painting works, brick works, and plaster works with activity risk score of 18.0, 16.0, and 13.125 respectively having risk rating level of “High” but for plumbing works it was “moderate risk level with risk score of 8.25. The riskiest activity for plumbing work had been revealed as Working in narrow space/ voids with risk score of 9.75 having risk rating level of “Moderate”. Lifting up of construction materials to working platform had been revealed as another common activity for painting works, brick works, and plaster works with respective risk score of 12.25, 14.0, 12.25 having risk level rating of “High”. Storing materials over platform of scaffolding had been revealed as the another common activity with respective risk score and risk level 11.375 “Moderate” for painting works, 13.125 “High” for brick work, and 9.75 “Moderate” for plaster works. Painting in required pattern, use of faulty tools, sanding/ scrubbing wall surface for painting, blending of paints were another activities in painting works with “Moderate” risk level rating and respective risk score of 10.5, 9.0, 8.0, and 6.0. For brick work in high-rise building, cutting/ breaking/ drilling, using faulty tools, and brick laying in line were the another activity in with “Moderate” risk level rating and respective risk score of 11.25, 9.0, and 6.9. For plaster work in high-rise building, plastering in required line and level, cutting/ breaking/ drilling, using faulty tools, were the another activity with “Moderate” risk level rating and respective risk score of 10.50, 9.0, and 8.0. The management commitment to the job safety along with worker participation is essential for successful construction project. Preventive and control measures should be planned and implemented as per the risk level assessed for prevailing hazards.